Key Determinants of Corporate Investment Efficiency - Wisnantiasri, Sila Ninin; Widiastuti, Yeni; Dwirini (Indonesian Journal of Business Analytics, 2025)
The efficient allocation of capital to value-enhancing investment is a crucial concern of accounting finance practices. Over the past decades, a growing body of research has studied the factors of investment efficiency, yet a comprehensive synthesis remains limited. This study employs the Kitchenham systematic literature review methodology and citation analysis. By analyzing 65 peer-reviewed articles from the Scopus database that addressed investment efficiency, we identify eight major determinants depending on the method and contextual setting employed: financial reporting and accounting quality, corporate governance and CSR, government intervention and policy, ownership structure, industry and sector-specific, international and emerging markets, and methodological approaches and theoretical advancements. It contributes a more comprehensive understanding of the mechanism driving investment efficiency and optimizing capital allocation.